Impact of ionic liquid's cation alkyl chain length and reaction time on cellulose nanocrystals preparation - da Silva, Jania Betania Alves; Vieira, Suellen Rocha; Pessôa, Luiggi Cavalcanti; Santana, Jamille Santos; Lemos, Paulo Vitor França; Souza, Carolina Oliveira de; Cardoso, Lucas Guimarães; Assis, Denílson de Jesus; Mussagy, Cassamo Ussemane; Santos‑Ebinuma, Valéria Carvalho [UNESP] (Elsevier, 2023)
Traditional methods to obtain cellulose nanocrystals typically involve mechanical and chemical processes and develop an improved process in terms of efficiency, sustainability, and the quality of CNCs produced are interesting. In this sense, we aimed to prepare cellulose nanocrystals (CNCs) from the hydrolysis of microcrystalline cellulose using protic ionic liquids (PILs), named 3-diethylamino-propylammonium hexanoate ([DEAPA][Hex]), 3-dimethylamino- 1-propylammonium hexanoate ([DMAPA][Hex]), and propylammonium hexanoate ([PA][Hex]) at different reaction times. The PILs demonstrated efficiency in producing cellulose nanocrystals, regardless of the cation size and reaction times. However, as expected the properties of the CNCs varied depending on the studied condition. The highest yield was observed in DMAPA[Hex], with a 34 % conversion. Crystalline indices decreased independent of the cation sizes and reaction times. Thermal stabilities were shifted to higher temperatures up to 92 ºC probably due to PILs cation sizes. In contrast, increasing reaction times decreased nanocrystals’ thermal stabilities up to 51ºC. So, protic ionic liquids (PILs) can be considered more environmentally friendly or sustainable solvents compared to traditional organic solvents for preparing cellulose nanocrystals. In the present work, it is reported an alternative method for obtaining CNCs and additionally provide the best preparation conditions for achieving important properties of this nanomaterial, with the potential for various applications.
Keywords: Cellulose nanoparticles; Hydrolysis; Microcrystalline cellulose; Protic ionic liquids